2021
DOI: 10.1002/mds.28467
|View full text |Cite
|
Sign up to set email alerts
|

Differentially Expressed Circular RNAs in Peripheral Blood Mononuclear Cells of Patients with Parkinson's Disease

Abstract: Background New noninvasive and affordable molecular approaches that will complement current practices and increase the accuracy of Parkinson's disease (PD) diagnosis are urgently needed. Circular RNAs (circRNAs) are stable noncoding RNAs that accumulate with aging in neurons and are increasingly shown to regulate all aspects of neuronal development and function. Objectives Τhe aims of this study were to identify differentially expressed circRNAs in blood mononuclear cells of patients with idiopathic PD and exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 89 publications
0
50
0
Order By: Relevance
“…However, the expression of circRNA peripheral blood mononuclear cells of patients diagnosed with PD has been investigated. Among the six aberrantly expressed circRNA, four could distinguish PD from healthy control ( Ravanidis et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the expression of circRNA peripheral blood mononuclear cells of patients diagnosed with PD has been investigated. Among the six aberrantly expressed circRNA, four could distinguish PD from healthy control ( Ravanidis et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Differentially expressed circRNAs in PBMCs have also been studied in PD patients and have been considered as possible biomarkers for the diagnosis of PD. Ravanidis et al ( 2021 ) enrolled 60 PD patients and 60 healthy controls to compare circRNA expression between the two groups via microarray analysis, which showed that six circRNAs were obviously decreased. In order to further evaluate the diagnostic value of the differentially expressed circRNAs in PD patients, receiver operating characteristic (ROC) curves were performed, and the area under the curve (AUC) was calculated to evaluate the predictive sensitivity and specificity of PBMC circRNAs for PD diagnosis.…”
Section: Circrnas As Biomarkers In Ad and Pdmentioning
confidence: 99%
“…For example, Cressatti et al, found that salivary miRNA-153 and miRNA-223 may be able to distinguish PD patients from controls with an area under the curve of 79% (95% confidence interval (CI), 64.5-99.2) and 74% (95% CI, 59.6-93.0), respectively [29]. Similarly, Ravanidis and colleagues identified six circRNAs that may be deregulated in PD patients [30]. The authors combined four of these into one biomarker, which in the same patients had a sensitivity of 75.3%, a specificity of 78%, and an area under the curve of 0.84.…”
Section: Transcriptomic Biomarkersmentioning
confidence: 99%